2024
DOI: 10.1088/2057-1976/ad33a9
|View full text |Cite
|
Sign up to set email alerts
|

A microdosimetry analysis of reversible electroporation in scattered, overlapping, and cancerous cervical cells

Mayank Kumar,
Ashutosh Mishra

Abstract: We present a numerical method for studying reversible electroporation on normal and cancerous cervical cells. This microdosimetry analysis builds on a unique approach for extracting contours of free and overlapping cervical cells in the cluster from the Extended Depth of Field (EDF) images. The algorithm used for extracting the contours is a joint optimization of multiple-level set function along with the Gaussian mixture model and Maximally Stable Extremal Regions. These contours are then exported to a multi-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Their initial study on the local analysis of a planar membrane could predict highly non-linear pore formation and growth and the simultaneous coupled variation of the transmembrane potential. The physics of electroporation on a cellular level can be much more complex than those of a local small planar patch of the membrane, predominantly on account of spatial variation of the electric field [26, 7, 27, 18]. Using computational simulations, a number of studies demonstrated that for spherical biological cells, the TMP, pore number, and pore size are nonlinearly coupled, resulting in nonintuitive transient variations in TMP along the membrane [17, 14, 11, 34, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Their initial study on the local analysis of a planar membrane could predict highly non-linear pore formation and growth and the simultaneous coupled variation of the transmembrane potential. The physics of electroporation on a cellular level can be much more complex than those of a local small planar patch of the membrane, predominantly on account of spatial variation of the electric field [26, 7, 27, 18]. Using computational simulations, a number of studies demonstrated that for spherical biological cells, the TMP, pore number, and pore size are nonlinearly coupled, resulting in nonintuitive transient variations in TMP along the membrane [17, 14, 11, 34, 13].…”
Section: Introductionmentioning
confidence: 99%